Contribution of selected lichens species of the genus Cladonia on the heathlands in Toruń (N, Poland) - Adamska, Edyta; Filbrandt-Czaja, Anna; Richert, Agnieszka (Ecological Questions, 2018)
The study presents data on the distribution of selected species of lichens – Cladonia furcata (Huds.) Schrad., C. rangiferina (L.) Weber ex F.H. Wigg. and C. uncialis (L.) Weber ex F.H. Wigg. in Toruń and along its southern boundary - on a heathland on the military training ground. A comparison was carried out of the research findings on the occurrence of the analysed species against variable habitat conditions over a period of nearly 40 years. The occurrence of Cladonia uncialis was most frequently observed within the city, in the habitats of Calluna vulgaris. A tendency was shown of selected lichen species to spread in the investigated area.